The Formation of Networks with Transfers among Players - Matthew O. Jackson; Francis Bloch (Fondazione Eni Enrico Mattei (FEEM), 2004)
We examine the formation of networks among a set of players whose payoffs depend on the structure of the network. We focus on games where players may bargain by promising or demanding transfer payments when forming links. We examine several variations of the transfer/bargaining aspect of link formation. One aspect is whether players can only make and receive transfers to other players to whom they are directly linked, or whether they can also subsidize links that they are not directly involved in. Another aspect is whether or not transfers related to a given link can be made contingent on the full resulting network or only on the link itself. A final aspect is whether or not players can pay other players to refrain from forming links. We characterize the networks that are supported under these variations and show how each of the above aspects is related either to accounting for a specific type of externality, or to dealing with the combinatorial nature of network payoffs.
Keywords: A14; C71; C72; 330; Networks; Network games; Network formation; Game theory; Efficient networks; Side payments; Transfers; Bargaining; Externalities; Netzwerk; Spieltheorie; Netzwerkökonomik